2012
DOI: 10.1182/blood.v120.21.1280.1280
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Targets of MLL-AF9 in a Novel Conditional Mouse Model

Abstract: 1280 Previous studies have shown that the expression of several leukemia-associated mixed lineage leukemia (MLL) fusion genes transformed human and mouse bone marrow cells in vitro and in vivo. In order to dissect the molecular and cellular targets of the MLL-AF9 fusion, we generated a novel inducible doxycycline (DOX)-regulated transgenic mouse model. Conditional ex vivo activation of MLL-AF9 induced aberrant self-renewal and impaired differentiation of long-term or short-term hematopoietic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Increased FUT4 RNA also is included in the signature that clusters MLL-r leukemias together from other subclasses [3] and was suggested to regulate migration and adhesion of B-ALL cells by integrin α5β1 [76]. Thus, we believe that increased Lewis X synthesis could contribute to MLL-AF4-driven migration and invasion [77].…”
Section: Discussionmentioning
confidence: 82%
“…Increased FUT4 RNA also is included in the signature that clusters MLL-r leukemias together from other subclasses [3] and was suggested to regulate migration and adhesion of B-ALL cells by integrin α5β1 [76]. Thus, we believe that increased Lewis X synthesis could contribute to MLL-AF4-driven migration and invasion [77].…”
Section: Discussionmentioning
confidence: 82%
“…The present study found that embryonic development-related genes were prognostic risk factors for BLCA. Invasion and metastasis of BLCA are thought to be associated with EMT [30,31].Tumor cell stemness regulates tumor cell differentiation, proliferation, invasion and migration [4,[32][33][34].Numerous studies showed that cancer stem cells regulate EMT [35][36][37].Embryonic development is often closely related to stem cells and EMT [5,38,39]. Therefore, we established a micro-landscape of embryonic development-related genes for predicting prognostic risk in BLCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…To conceptually validate the presence of inflammation in HSPCs beyond the C1498 model system, we utilized a more commonly used and translationally relevant MLL-AF9 AML mouse model (27,28). Typically reliant of retrovirus overexpression, the model system we describe here mimics human disease instead through doxycycline (DOX) mediated regulation of human MLL-AF9 fusion oncogene expression to (29,30). To evaluate the inflammatory state in HSPCs in the iMLL-AF9 model in vivo, we generated chimeric recipients (CD45.2) bearing both iMLL-AF9 BM (CD45.1; iMLL-AF9 leukemic BM) and wildtype BM (CD45.1/2; resembling healthy BM) (Fig.…”
Section: The Transcriptome Of Hematopoietic Stem and Progenitor Cells...mentioning
confidence: 99%